Can optical coherence tomography angiography be a first line ophthalmological evaluation in patients with Behçet’s disease? - Dilhan Karaca; Aynur Dıraçoğlu; Feyza Önder (Archives of Rheumatology, 2023)
Objectives: This study aimed to investigate whether early ocular findings can be demonstrated with optical coherence tomography angiography in patients with Behçet’s disease. Patients and methods: Thirty-seven eyes of 22 patients with Behçet’s disease with ocular involvement, 48 eyes of 26 Behçet patients without any ocular involvement, and 44 eyes of 22 healthy controls were included, for a total of 70 patients (39 males, 31 females; mean age: 42.3±11.7 years; range, 18 to 65 years), in the cross-sectional study conducted between September 2019 and April 2020. The parameters analyzed were the foveal avascular zone (FAZ), central macular thickness, total deep capillary plexus vessel density (DCPVD), parafoveal deep capillary plexus vessel density (PaDCPVD), total superficial capillary plexus vessel density (SCPVD), and parafoveal superficial capillary plexus vessel density (PaSCPVD). Results: Total DCPVD, total SCPVD, PaDCPVD, and PaSCPVD were found to be low in the ocular involvement group compared to the others, and the FAZ area was larger compared to the control group. Capillary plexus densities were positively correlated with the best-corrected visual acuity and negatively correlated with disease duration. No statistically significant difference was found between patients with Behçet without ocular involvement and the control group in terms of the FAZ area, DCPVD, PaDCPVD, SCPVD, and PaSCPVD. Conclusion: Optical coherence tomography angiography demonstrated decreased vascularity in Behçet patients with ocular involvement; however, it revealed no microvascular differences between patients with Behçet’s disease who do not have ocular involvement and the control group.